Correlation between cystasin C to disease severity of cirrhosis on model of end stage liver disease score - Gunadi, Heribertus; Bayupurnama, Putut; Nurdjanah, Siti (Acta Interna The Journal of Internal Medicine, 2011)
ABSTRACTBackground:    Cirrhosis patients  with renal failure  are  at   high   risk  for   death   and  reduced survival   as   compared   with   those   without   renal failure,  and have poor prognosis.  Some studies  have suggested   that  cystatin  C did  more  accurate   than creatinine /0  detect glomerulusfiltration    rate (GFR) in patients  with cirrhosis.  Model  of End Stage  Liver Disease  (MELD)  score  can be used in patients  with cirrhosis  with variously  Widely severity  disease  and etiologies.  Until nmv, there is no study about correlation  between  levels  of cystatin  C to disease severity  in cirrhosis based on MELD score.Objective:  This present  study  was to investigate  the correlation  between levels of cyst at ill C with disease severity  in cirrhosis  based on MELD score.Method:   Study  design  was cross sectional s t u d y,     This      study       was     conducted          at Gastoenterohepatology         outpatient     clinic    and Internal Medicine  ward of Dr Sardjito  General Hospital,     Yogyakarta.    Inclusion     criteria     were patients    with    cirrhosis    diagnosed     by   clinical criteria,  laboratory   and  USG.findillg,   age   >  18 years,   had  complete  medical  record  and  obtained informed consent. Exclusion criteria were chronic kidney  disease,  sepsis,  hepatocellutare   carcinoma, used high doses  of steroid,  had thyroid dysfunction. hypertension  and diabetes mellitus.Result:   The  mean  of cystatin   C based  on categorical    MELD    score   were   MELD    <10   = 0.93±0.19   mgll;   MELD    IO-19=1.08±0.26    mg/l; MELD  20-29   =  1.25±O.27 mgll;  MELD  30-39   = 2.49 mg/l and  MELD  >40  = 2.43 mgll;  0)=0.013; 95%   CI  0.000-0.061).     There   was   a  significant correlation   between  cystatin  C to MELD  score  as demonstrated   byp=O.OOOand r=0.485.Conclusion:     Our  data  suggested    a significant     correlation     with   medium    strength between cystatin  C to severity  disease  of cirrhosis based 011 MELD score. Keywords:  cirrhosis,  cystatin  C, MELD score